Overcoming methodological challenges in prevalence studies in developing contexts with vulnerable children. (May 2020) - Jordan, Lucy; Chui, Cheryl Hiu-Kwan; Larmar, Stephen; O'Leary, Patrick
Social work research concerns itself with vulnerable populations. Methodological challenges including accessing vulnerable populations are especially acute in developing countries where systematized data is often lacking. This article presents a pilot study using respondent-driven sampling to estimate the prevalence of children engaged in commercial sexual exploitation. The results are used to illustrate the feasibility of developing multi-sectoral collaborations to address issues among vulnerable populations. This study demonstrates that respondent-driven sampling is a strong design capable of producing prevalence estimates. Implications for international social workers in facilitating professional capacity building for effective planning, monitoring and reporting of social development projects are discussed.